Plant species richness records in Ukrainian steppes - Borovyk, Dariia; Dembicz, Iwona; Dengler, Jürgen; Guarino, Riccardo; Kuzemko, Anna; Kateryna Lavrinenko; Moysiyenko, Ivan; Skobel, Nadiia; Bednarska, Iryna; Babytskiy, Andriy; Безсмертна, Олеся Олексіївна; Larysa Borovyk; et al. (Floristisch - Soziologische Arbeitsgemeinschaft, 2024)
We compiled a list of the known maxima of vascular plant species richness in the steppe zone of Ukraine at different sampling scales (0.0001–100 m²) and compared them with the world records. Detailed information on each of the identified species-rich grassland plots is provided, including site descriptions, plot characteristics, coordinates, and species lists. Most of the small-scale records (up to 0.1 m²) were found in mesic grasslands in southern Ukraine (Kherson region) with a high abundance of annual grasses and forbs: 9 and 11 vascular plant species in 0.0001 m² and 0.001 m², respectively, in the steppe depression Chorna Dolyna, and 26 species in 0.1 m² in a mesic psammophytic grassland in the Dzharylhach National Nature Park. Most of the records at larger scales were made in the northern part of the steppe zone, in forb-rich and forb-grass steppes: 15, 39, 73, and 107 species in 0.01, 1, 10, and 100 m², respectively. All richness records were characterised by neutral to slightly alkaline substrates (soil pH 7.0–7.7) and low-intensity management. These characteristics are consistent with the known patterns from world records of species richness. Our inventory provides baseline knowledge for studies on the high species richness in the steppe zone and can stimulate the further investigation of identified species-rich grasslands, as well as the search for new ones. Since we did not specifically search for species-rich sites, and our dataset includes only a relatively small number of plots compared to similar studies in other regions, we expect that more species-rich vegetation will be found with further research. This study highlights the importance of steppe grasslands as global biodiversity hotspots and draws attention to their protection in the context of land-use changes and the consequences of the war in Ukraine.
Keywords: alpha diversity; biodiversity; grassland; maximum; spatial scale; species richness; steppe; Ukraine; vascular plant; vegetation plot